The Importance of Sports Participation on Lithuanian Adolescents' Social and Emotional Health - Lochbaum Marc; Lisinskiene Ausra; Sisneros Cassandra; Cooper Sydney; Paulauskas Rutenis; Majauskiene Daiva (Sciendo, 2024)
Global mental health rates are staggering. Youth mental health in sport is a topic with increasing research attention. To date, most youth sport research examines mental health from isolated events as opposed to a cumulative-assets framework. Our main research question examined sport participation group differences regarding four mental health domains; emotional competence, belief-in-others, belief-in-self, and engaged living, and the composite covitality meta-indicator. To answer our research questions, 1965 Lithuanian youths (60.10% female) ranging in age from 11 to 17 (M = 13.62, SD = 1.96) from urban and rural school districts completed our survey. Our results indicated many significant differences (p < 0.001) emerged for participant sex, age grouping, and sport participation (competitive, leisure, or none). Only for the sport participation were the MANOVA and ANOVA effect size values at least small in magnitude. In the follow-up analyses (all p's < 0.001), the competitive group differed from the no sport group (effect sizes medium-to-large) and to the leisure participant group (effect sizes small) in all four mental health domains and the meta-indicator covitality. Small-to-medium effect size values resulted between the leisure and no sport groups. Sport participation, even for leisure, is related to improved self-reported social and emotional health in our large sample. The practical implication is clear that all governments and such bodies should provide accessible and affordable sport participation opportunities, whether competitive or recreational. Longitudinal research, as a future direction in sport contexts, will help to best understand and move forward with youth mental health.